2019
DOI: 10.1021/acs.jpclett.9b00959
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Coupled Electron Transfer of Plastoquinone Redox Reactions in Photosystem II: A Pump–Probe Ultraviolet Resonance Raman Study

Abstract: Plastoquinones (PQs) act as electron and proton mediators in photosystem II (PSII) for solar-to-chemical energy conversion. It is known that the redox potential of PQ varies in a wide range spanning hundreds of millivolts; however, its structural origin is not known yet. Here, by developing a pump–probe ultraviolet resonance Raman technique, we measured the vibrational structures of PQs including QA and QB in cyanobacterial PSII directly. The conversion of QA to QA •– in the Mn-depleted PSII is verified by dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Furthermore, chromium and other trace elements may cause ultrastructure abnormalities in mesophyll cells and root cells ultimately increased metal deposition in some plant parts. Several previous studies have suggested the inhibitory effect of chromium on PSII activity mostly studies have been performed on cellular membrane damaging effect, to increase knowledge about the negative effect of chromium on photosynthesis PSII activity to evaluate the toxic effect of chromium on photosynthetic apparatus (Souri et al, 2019), Chromium stress induces changes in ultrastructure of chloroplast, electron transport chain (Chen et al, 2019). At PSII chromium ions replaces the co-factor Ca 2+ known to be very important for water-splitting, hence alters the structure and function of oxygen evolving complex.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, chromium and other trace elements may cause ultrastructure abnormalities in mesophyll cells and root cells ultimately increased metal deposition in some plant parts. Several previous studies have suggested the inhibitory effect of chromium on PSII activity mostly studies have been performed on cellular membrane damaging effect, to increase knowledge about the negative effect of chromium on photosynthesis PSII activity to evaluate the toxic effect of chromium on photosynthetic apparatus (Souri et al, 2019), Chromium stress induces changes in ultrastructure of chloroplast, electron transport chain (Chen et al, 2019). At PSII chromium ions replaces the co-factor Ca 2+ known to be very important for water-splitting, hence alters the structure and function of oxygen evolving complex.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus reasonable to attribute the shifts in the redox potential of Q A to the structural changes that occur upon Mn/Ca depletion or Ca 2+ /Sr 2+ exchanges [5,10,11,16]. Q A is stabilized by van der Waals interactions, including two moderate H-bonds between its carbonyl oxygen (C=O1, proximal; C=O2, distal) and N-Phe261-D2 and N δ -His214-D2, respectively, as well as a π-stacking interaction with the nearby highly conserved D2-Trp253 (Table 1; Figure 3) [2,17]. This interaction is similar to the corresponding native Q A interaction with slightly higher thermal motion, i.e., a 10%–20% increase in the temperature (B) factors (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the blooming publications on the organic synthetic methodologies promoted by PCET, the professional and deep experimental studies on PCET mechanism for revealing its fundamental rules are relatively rare in China, [151,[172][173][174][175] however, we are glad to see that more publications on theoretical studies have been published from Chinese groups in last five year. [173][174][175][176][177][178][179][180] Further explorations of PCET mechanism including how substrates and reaction conditions influence and regulate the PCET pathways, and so on, may provide novel ideas and methods for current synthetic methodology, and even help chemists discover unexpected patterns of chemical bond forming and breaking. Therefore, future works are supposed to focus on not only the synthetic applications, but also mechanism studies of PCET reactions, including new forms of PCET processes, which should benefit the development of other branches of chemistry.…”
Section: Discussionmentioning
confidence: 98%